Measuring transformational leadership style and its effectiveness on virtual work-teams in Mexico - Varela Medina, Néstor Daniel; González Macías, Carlos Jesús; Ochoa Meza, Gerardo (2020)
Objective: To examine transformational leadership factors that promote effectiveness in virtual work-team performance, generating empirical basis theoretical knowledge in management of virtual environments in Mexico. Method: Design and development of a questionnaire to assess determinants of transformational leadership and its effectiveness in virtual work-team performance. Results: this instrument is supported by evidences according to several perspectives founded at the conducted literature review. Limitations: this questionnaire do not use statistical productivity nor quality indicators in organizations. Originality: there is no instrument that address these factors in Mexico. Conclusions: this study will contribute to administrative sciences by developing an instrument to assess leadership capability and its effectiveness on virtual work team as new key parameters and strategies to be used by those business environment stakeholders.